1981
DOI: 10.1111/j.1530-0277.1981.tb04895.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Exposure to Ethanol Enhances Pituitary‐Adrenal and Temperature Responses to Etanol in Adult Rats

Abstract: Long lasting effects of perinatal ethanol exposure were studied in adult rats who were the offspring of dams fed a 5.0% w/v ethanol-containing liquid diet ad libitum or pair-fed the isocaloric control diet during gestation weeks 2 and 3 or during postnatal week 1. Fetal exposure to ethanol reduced body weight of pups at birth unless the ethanol diet was supplemented with casein; neonatal exposure to the ethanol or pair-fed diets, casein supplemented or not, reduced pup weights until day 21 postnatally when wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…Also, "anger-prone" 15 month-old infants exhibit augmented CORT response when confronted with a stranger or a frightening robot-toy (48). In rodents, FAexposure leads to either LHPA axis hyper-responsiveness to stressors or delayed or deficient return to pre-stress level (49,50,51,52,53,54,55,56). In this study, the effects of FA-exposure on increased infant irritability and LHPA axis responsiveness were most prominent in rhesus monkeys carrying the s allele.…”
Section: Discussionmentioning
confidence: 58%
“…Also, "anger-prone" 15 month-old infants exhibit augmented CORT response when confronted with a stranger or a frightening robot-toy (48). In rodents, FAexposure leads to either LHPA axis hyper-responsiveness to stressors or delayed or deficient return to pre-stress level (49,50,51,52,53,54,55,56). In this study, the effects of FA-exposure on increased infant irritability and LHPA axis responsiveness were most prominent in rhesus monkeys carrying the s allele.…”
Section: Discussionmentioning
confidence: 58%
“…This relationship seems to be mediated by different hormonal and neurochemical systems, such as the HPA axis and the pituitary Beta-endorphin system. Prenatal ethanol exposure alters levels of adrenocorticotropin hormone (ACTH) and corticosterone (Taylor et al, 1981;Taylor et al, 1988;Weinberg, 1989;Weinberg et al, 1996) as well as Beta-endorphins (Angelogianni and Gianoulakis, 1989) in response to different stressors. As mentioned earlier, in one study higher ethanol consumption was observed in rats prenatally exposed to the drug, but only after chronic stress (Nelson et al, 1983).…”
Section: Alterations In the Stress Responsementioning
confidence: 99%
“…When rats are exposed to high ethanol doses throughout the last two weeks of the gestation, long-lasting effects upon the activity of the hypothalamic-pituitary-adrenal axis (HPA) are consistently observed (Taylor, Branch, Liu, & Kokka, 1982;Taylor et al, 1981;Weinberg, Taylor, & Gianoulakis, 1996). This prenatal treatment induces heightened responsiveness to various stressors, a phenomenon that could eventually predispose the organism to use or abuse ethanol as a means of alleviating stressrelated negative states (e.g.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%